Core-shell structure hydrogen anion conductor and preparation method and application thereof

By constructing a hydrogen negative ion conductor with a core-shell structure, using rare earth metal hydride as the core and high-electronic resistance materials as the shell, the existing hydrogen negative ion conductors are solved in the problem of insufficient conductivity at medium and low temperatures, and excellent hydrogen negative ion conductivity is achieved, expanding its application potential in the field of electrochemistry.

CN119724691APending Publication Date: 2025-03-28DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311279122.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing hydrogen negative ion conductors have poor ion conductors at medium and low temperatures, and because hydrogen negative ions are prone to dissociation of electrons, the materials often have high electronic conductivity, resulting in limited applications in the field of electrochemistry.

Method used

By constructing a hydrogen negative ion conductor with a core-shell structure, the core part is a rare earth metal hydride, and the shell is a material with high electron resistance, such as alkali metal hydride or oxide, which significantly inhibits the electronic conductance of the core material and retains efficient hydrogen negative ion conduction.

Benefits of technology

It achieves excellent hydrogen negative ion conductivity at room temperature and medium and low temperatures, broadens the research system and application scope of solid electrolyte materials, and has the potential to be applied to new secondary batteries, fuel cells and electrochemical reaction devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119724691A_ABST
    Figure CN119724691A_ABST
Patent Text Reader

Abstract

The invention discloses a core-shell structure hydrogen anion conductor and a preparation method and application thereof, the core-shell structure hydrogen anion conductor comprises a core part and a coating layer, and the core part is coated with the coating layer. The invention constructs a hydrogen anion conductor with a core-shell structure, the core is a mixed ion conductor for conducting hydrogen anions, and the shell layer is a material with relatively large electronic resistance. The material shows excellent ionic conductivity at room temperature and high temperature, and is expected to be applied to hydrogen anion batteries, fuel cells, electroreduction reaction devices and the like. According to the invention, the research system of metal hydride and solid electrolyte materials and the application range of the research system are greatly widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a core-shell structured hydrogen anion conductor and a preparation method and application thereof, belonging to the technical field of new energy and solid electrolytes. Background Art

[0002] Can conduct Li + 、Na + , H + , O 2- Various ion conductors of plasma have been widely used in secondary batteries, fuel cells, electrochemical reactions, separation membranes, sensors and other fields. - / H2 has a redox potential of up to -2.3V. Hydrogen ion conductors can be used to construct new hydrogen ion batteries and fuel cells, and they also have the potential to be used as electrolytes for electrochemical reduction reactions of small molecules (such as CO2, N2, etc.). Some hydrogen ion conductors have been reported, mainly including two categories: one is based on alkaline earth metals, including binary hydrides, oxyhydrides, and halogen hydrides; the other is based on rare earth metals, mainly oxyhydrides and pure hydrides. There are still few research systems for hydrogen ion conductors, and most systems have poor ionic conductivity at medium and low temperatures and room temperature. In addition, since hydrogen ions easily dissociate electrons, the materials often have high electronic conductivity, resulting in their application in the field of electrochemistry. It is still very challenging to achieve high pure hydrogen ion conduction at medium and low temperatures.

[0003] As early as the 1990s, the rapid diffusion of hydrogen in rare earth hydrides was discovered. Recent studies have shown that rare earth metal hydride lanthanum hydride can be used as a hydride conductor and exhibits excellent performance at both room temperature and low temperature, but its temperature operating range is narrow and its thermal stability is poor. In addition, the electronic conductivity of rare earth metal hydrides is large, which is not conducive to the realization of pure hydride conduction. Alkaline earth metal hydrides have shown that they can be used as hydride conductors as early as the last century, but their operating temperature is relatively high. A large number of studies have focused on the synthesis of new materials, while there are few reports on adjusting special composite structures to achieve hydride conduction. Summary of the invention

[0004] The present invention constructs a special core-shell structure to enable it to exhibit excellent hydrogen anion conductivity at room temperature and medium and low temperatures. This invention will greatly broaden the research system and application scope of solid electrolyte materials.

[0005] The present invention provides a novel structure of hydrogen anion conductor. Specifically, a core-shell microstructured hydrogen anion conductor is constructed, the particle core of which is a mixed hydrogen anion conductor and the shell is a material with high electronic resistance. It exhibits excellent ionic conductivity at room temperature and high temperature.

[0006] The core material is mainly rare earth metal hydride, which can show good hydrogen migration at room temperature and has high hydrogen ion conductivity; but their electronic conductivity is also very high, often at the same order of magnitude as ion conductivity or even higher. Therefore, there was no way to use it as a hydrogen ion conductor before. Our core-shell structure can greatly suppress the electronic conductivity of the core material while retaining considerable hydrogen ion conduction. Coating material: mainly materials with very low electronic conductivity, preferably insulators, whose electronic conductivity is more than 2 orders of magnitude lower than that of the core material, so as to suppress the electron transfer of the core. Such as alkaline (earth) metal hydrides, oxides, etc.

[0007] According to one aspect of the present application, a core-shell structured hydrogen anion conductor is provided, the core-shell structured hydrogen anion conductor comprising a core portion and a coating layer, wherein the coating layer is coated on the core portion;

[0008] The core part is a mixed ion conductor that conducts negative hydrogen ions.

[0009] Optionally, the carriers of the mixed ion conductor are electrons and negative hydrogen ions, and the ion mobility number thereof is 0.01 to 0.99.

[0010] Optionally, the core portion is a particle with a diameter of 0.01 nm to 1 mm.

[0011] Optionally, the core diameter is selected from any value among 0.01 nm, 0.05 nm, 0.1 nm, 0.5 μm, 1 μm, 5 μm, 10 μm, 100 μm, 1 mm or a range between any two of the above values.

[0012] Optionally, the coating layer has a thickness of 0.001 nm to 1 mm.

[0013] Optionally, the thickness of the coating layer is selected from any value of 0.001 nm, 0.01 nm, 0.1 nm, 1 nm, 10 nm, 1 μm, 10 μm, 1 mm, or a range between any two of the above values.

[0014] Optionally, the electronic resistivity of the coating layer at the operating temperature is 100 to 100,000 times that of the core portion.

[0015] Optionally, the electronic conductivity of the coating layer is 0.001 to 1000 S cm -1 .

[0016] Optionally, the resistivity of the core is 10 -10 ~0.001S cm -1 .

[0017] In the present application, a core-shell microstructured hydrogen anion conductor is constructed, wherein the particle core of the material is a mixed hydrogen anion conductor and the shell is a material with high electronic resistance; the core size of the heterostructure is 0.01nm~1mm, and the size of the coating layer is 0.001nm~1mm.

[0018] Optionally, the carriers of the mixed ion conductor are electrons and negative hydrogen ions, and the ion mobility number thereof is 0.01 to 0.99.

[0019] Optionally, within the operating temperature range, the electronic resistivity of the cladding material is more than 100 times the resistivity of the core material.

[0020] Optionally, the covering may be full covering or partial covering.

[0021] Optionally, the core material and the cladding material may be in a single phase, or in a multi-phase or amorphous state.

[0022] According to another aspect of the present application, a method for preparing the above-mentioned hydrogen anion conductor is provided, the preparation method comprising:

[0023] A mixture containing rare earth metal hydride and main group metal compound is mixed to obtain the core-shell structured hydrogen anion conductor;

[0024] The main group metal compound is an alkali metal compound and / or an alkaline earth metal compound.

[0025] Optionally, the mixed construction method is selected from at least one of ball milling, grinding, wet chemical method, and vapor deposition method.

[0026] Optionally, the ball milling conditions are: the ball milling speed is 50 to 500 rpm, and the ball-to-mass ratio is 1:1 to 100:1.

[0027] Optionally, the rotation speed of the ball mill is selected from any value of 50 rpm, 100 rpm, 150 rpm, 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm or a range between any two of the above.

[0028] Optionally, the spherical-to-mass ratio is selected from any value of 1:1, 5:1, 10:1, 20:1, 30:1, 50:1, 80:1, 100:1 or a range between any two of the above values.

[0029] Optionally, the ball milling atmosphere has a partial pressure of 0.1 to 100 bar, and the ball milling time is 0.1 to 60 h.

[0030] Optionally, the partial pressure of the ball milling atmosphere is selected from any value among 0.1 bar, 0.5 bar, 1 bar, 5 bar, 10 bar, 20 bar, 30 bar, 50 bar, 80 bar, 100 bar or a range between any two of the above values.

[0031] Optionally, the grinding atmosphere is selected from hydrogen and / or argon.

[0032] Optionally, the condition of the wet chemical method is: the mixture contains a solvent, and the solvent is selected from at least one of tetrahydrofuran, cyclohexane, and benzene.

[0033] Optionally, the reaction temperature in the wet chemical method is -100 to 900°C.

[0034] Optionally, the reaction temperature in the wet chemical method is selected from any value of -100°C, 0°C, 10°C, 50°C, 100°C, 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C or a range between any two of the above.

[0035] Optionally, the reaction atmosphere in the wet chemical method is selected from hydrogen and / or argon.

[0036] Optionally, the conditions of the vapor deposition method are: the temperature is -100 to 900° C., and the deposition atmosphere is selected from hydrogen and / or argon.

[0037] In the present application, the method for preparing the core-shell structured hydrogen anion conductor comprises the following steps:

[0038] The required raw material powders are constructed into hydrogen anion conductor powders with a composite core-shell structure by mechanical ball milling, simple grinding and mixing, wet chemical method, vapor deposition and other methods; the obtained powders are extruded or calcined.

[0039] Optionally, the structure construction method includes at least one of mechanical ball milling, simple grinding and mixing, wet chemical method, vapor deposition, etc.

[0040] Optionally, the method of processing the core-shell structure powder to form a hydrogen anion conductor is extrusion molding or calcination and sintering.

[0041] Optionally, the method of processing the core-shell structured powder to form a hydrogen anion conductor is powder extrusion molding or calcination molding.

[0042] Optionally, the method further comprises installing electrodes at both ends of the extruded or calcined hydrogen anion conductor.

[0043] According to another aspect of the present application, there is provided an application of the core-shell structured hydrogen anion conductor described above in a novel secondary battery, a fuel cell, a hydrogen separation membrane, a sensor, and a membrane reactor.

[0044] The present application also proposes the use of the above-mentioned hydrogen anion conductor in constructing a new type of secondary battery, fuel cell, electrochemical reaction device, hydrogen separation membrane, sensor, and membrane reactor; wherein, the pure rare earth metal binary hydride conductor is used to construct a new type of secondary battery, fuel cell, and electrochemical reaction device. The mixed metal binary hydride conductor is used for hydrogen separation membrane, sensor, and membrane reactor.

[0045] Hydrogen ion (H - ) has strong reducing properties and high redox potential, is a highly reactive hydrogen source, and is a new type of energy carrier with great development potential. Hydrogen ion conductors have broad application prospects in research fields such as secondary batteries, fuel cells, electrochemical reactions, and hydrogen separation membranes. The present invention proposes a hydrogen ion conductor with a core-shell structure, in which the core is a mixed ion conductor that conducts hydrogen ions, and the shell is a material with large electronic resistance. It exhibits excellent ionic conductivity at room temperature and high temperature, and is expected to be applied to hydrogen ion batteries, fuel cells, and electric reduction reaction devices. This invention will greatly broaden the research system and application scope of metal hydrides and solid electrolyte materials.

[0046] The beneficial effects of this application include:

[0047] This application is the first to use a composite material with a core-shell structure as a hydrogen anion conductor, broadening the research scope of solid electrolyte systems. The hydrogen anion conductor developed by this method has excellent room temperature and even high temperature conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is a schematic diagram of the structure of the core-shell structure powder described in Example 1 of the present application.

[0049] Figure 2 5nm electron microscope image and element distribution of electron energy loss spectrum of the powder synthesized in Example 1 of the present application.

[0050] Figure 3 This is a curve showing the change of ionic conductivity with temperature in Example 1 of the present application. DETAILED DESCRIPTION

[0051] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0052] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0053] The instrument used in this application is: BioLogic VSP-300 electrochemical workstation.

[0054] The present invention adopts a mixed hydrogen ion conductor and a compound or single substance with high electronic resistance as a precursor, synthesizes a hydrogen ion conductor material having a core-shell structure complex as a main material through various physical and chemical methods, and studies the performance and application of the hydrogen ion conductor.

[0055] Example 1

[0056] This embodiment provides a CeH3@BaH2 core-shell structure hydrogen anion conductor, and the preparation method is as follows:

[0057] (1) 2 g of CeH3 and 0.648 g of barium hydride were weighed in a glove box and placed in a ball mill. The atmosphere in the ball mill was Ar and the mill was milled for 10 h at a speed of 300 rpm. After running for 10 min, the mill stopped for 2 min and rotated in the opposite direction. The schematic diagram of the powder microstructure is as follows: Figure 1 , the electron microscope microscopic image and its element distribution are Figure 2 ;from Figure 1 It can be seen that cerium hydride is the core, and barium hydride with high electronic resistance is the coating layer; Figure 2 It can be seen that the size of the core-shell structure particles formed is about 10 nanometers, the main phase is cerium hydride crystals, and the corresponding element distribution shows that barium is enriched on the surface of the particles, while cerium is concentrated in the core.

[0058] (2) Take 400 mg of the reaction product of step (1) and use a hydraulic press to press the powder into a sheet with a diameter of 10 mm and a thickness of about 1 mm at a pressure of 100 MPa.

[0059] (3) The thin sheet obtained in step (2) was loaded into a stainless steel battery buckle. Nickel foam was used as electrodes on both sides of the thin sheet to increase the contact area and reduce the contact resistance. The impedance spectrum and DC polarization curve of the battery buckle were tested using an electrochemical workstation. The test temperature ranged from 20°C to 260°C, and one point was measured every 20°C. Each temperature point was kept constant for 2 hours before testing again. The curve of ionic conductivity changing with temperature is shown in Figure 3 As shown. Figure 3 It can be seen that the ionic conductivity of the sample performs well in the range from room temperature to 240 degrees Celsius.

[0060] Example 2

[0061] This embodiment provides a CeH3@BaO core-shell structure hydrogen anion conductor, and the preparation method is as follows:

[0062] (1) In a glove box, weigh 2 g of metallic Ce and 0.648 g of barium oxide, put them into a ball mill, fill the mill with 20 bar of H2, and mill for 10 h at a speed of 300 rpm. After every 10 min of operation, stop for 2 min and rotate in the opposite direction.

[0063] (2) 400 mg of the reaction product of step (1) was taken and the powder was pressed into a sheet with a diameter of 10 mm and a thickness of about 1 mm using a hydraulic press at a pressure of 100 MPa;

[0064] (3) The thin sheet obtained in step (2) is loaded into a stainless steel battery buckle. Nickel foam is used as electrodes on both sides of the thin sheet to increase the contact area and reduce the contact resistance. The impedance spectrum and DC polarization curve of the battery buckle are tested using an electrochemical workstation. The test temperature ranges from 20°C to 260°C, and one point is measured every 20°C. Each temperature point is kept constant for 2 hours before testing again.

[0065] Example 3

[0066] This embodiment provides a CeH3@BaH2 core-shell structure hydrogen anion conductor, and the preparation method is as follows:

[0067] (1) In a glove box, weigh 2 g of metallic CeH3 and 0.648 g of barium hydride, put them into a mortar, and grind them by hand for 1 hour under an argon atmosphere;

[0068] (2) 400 mg of the reaction product of step (1) was taken and the powder was pressed into a sheet with a diameter of 10 mm and a thickness of about 1 mm using a hydraulic press at a pressure of 100 MPa;

[0069] (3) The thin sheet obtained in step (2) is loaded into a stainless steel battery buckle. Nickel foam is used as electrodes on both sides of the thin sheet to increase the contact area and reduce the contact resistance. The impedance spectrum and DC polarization curve of the battery buckle are tested using an electrochemical workstation. The test temperature ranges from 20°C to 260°C, and one point is measured every 20°C. Each temperature point is kept constant for 2 hours before testing again.

[0070] Example 4

[0071] This embodiment provides a LaH3@BaH2 core-shell structure hydrogen anion conductor, and the preparation method is as follows:

[0072] (1) In a glove box, weigh 2 g of metallic LaH3 and 0.648 g of barium hydride, mix them in THF liquid, seal and shake for 20 hours, and filter and dry the product under argon atmosphere;

[0073] (2) 400 mg of the reaction product of step (1) was taken and the powder was pressed into a sheet with a diameter of 10 mm and a thickness of about 1 mm using a hydraulic press at a pressure of 100 MPa;

[0074] (3) The thin sheet obtained in step (2) is loaded into a stainless steel battery buckle. Nickel foam is used as electrodes on both sides of the thin sheet to increase the contact area and reduce the contact resistance. The impedance spectrum and DC polarization curve of the battery buckle are tested using an electrochemical workstation. The test temperature ranges from 20°C to 260°C, and one point is measured every 20°C. Each temperature point is kept constant for 2 hours before testing again.

[0075] Example 5

[0076] This embodiment provides a CaH2@BaO core-shell structure hydrogen anion conductor, and the preparation method is as follows:

[0077] (1) Using calcium hydride as a substrate, barium oxide was deposited onto CaH2 in a glove box;

[0078] (2) 400 mg of the reaction product of step (1) was taken and the powder was pressed into a sheet with a diameter of 10 mm and a thickness of about 1 mm using a hydraulic press at a pressure of 100 MPa;

[0079] (3) The thin sheet obtained in step (2) is loaded into a stainless steel battery buckle. Nickel foam is used as electrodes on both sides of the thin sheet to increase the contact area and reduce the contact resistance. The impedance spectrum and DC polarization curve of the battery buckle are tested using an electrochemical workstation. The test temperature ranges from 20°C to 260°C, and one point is measured every 20°C. Each temperature point is kept constant for 2 hours before testing again.

[0080] Example 6

[0081] This embodiment provides a PrH3@MgO core-shell structure hydrogen anion conductor, and the preparation method is as follows:

[0082] (1) In a glove box, weigh 2 g of PrH3 and 0.648 g of magnesium oxide, put them into a ball mill, and place them in an Ar atmosphere. Mill for 10 h at a speed of 300 rpm. After every 10 min of operation, stop for 2 min and rotate in the opposite direction.

[0083] (2) 400 mg of the reaction product of step (1) was taken and the powder was pressed into a sheet with a diameter of 10 mm and a thickness of about 1 mm using a hydraulic press at a pressure of 100 MPa;

[0084] (3) The thin sheet obtained in step (2) is loaded into a stainless steel battery buckle. Nickel foam is used as electrodes on both sides of the thin sheet to increase the contact area and reduce the contact resistance. The impedance spectrum and DC polarization curve of the battery buckle are tested using an electrochemical workstation. The test temperature ranges from 20°C to 260°C, and one point is measured every 20°C. Each temperature point is kept constant for 2 hours before testing again.

[0085] Example 7

[0086] This embodiment provides a BaClH@BaH2 core-shell structure hydrogen anion conductor, and the preparation method is as follows:

[0087] (1) In a glove box, weigh 3 g of BaClH and 0.648 g of barium hydride, put them into a ball mill, fill the ball mill with 20 bar of H2, and ball mill for 10 h at a speed of 300 rpm. After running for 10 min, stop for 2 min and rotate in the opposite direction;

[0088] (2) 400 mg of the reaction product of step (1) was taken and the powder was pressed into a sheet with a diameter of 10 mm and a thickness of about 1 mm using a hydraulic press at a pressure of 100 MPa;

[0089] (3) The thin sheet obtained in step (2) is loaded into a stainless steel battery buckle. Nickel foam is used as electrodes on both sides of the thin sheet to increase the contact area and reduce the contact resistance. The impedance spectrum and DC polarization curve of the battery buckle are tested using an electrochemical workstation. The test temperature ranges from 20°C to 400°C, and one point is measured every 20°C. Each temperature point is kept constant for 2 hours before testing again.

[0090] Example 8

[0091] This embodiment provides a BaLiOH@MgO core-shell structure hydrogen anion conductor, and the preparation method is as follows:

[0092] (1) In a glove box, weigh 2 g of BaLiOH and 0.648 g of MgO, put them into a mortar, and grind them by hand for 1 h under argon atmosphere;

[0093] (2) 400 mg of the reaction product of step (1) was taken and pressed into a sheet with a diameter of 10 mm and a thickness of about 1 mm using a hydraulic press at a pressure of 100 MPa;

[0094] (3) The thin sheet obtained in step (2) is loaded into a stainless steel battery buckle. Nickel foam is used as electrodes on both sides of the thin sheet to increase the contact area and reduce the contact resistance. The impedance spectrum and DC polarization curve of the battery buckle are tested using an electrochemical workstation. The test temperature ranges from 20°C to 260°C, and one point is measured every 20°C. Each temperature point is kept constant for 2 hours before testing again.

[0095] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A core-shell structure hydrogen anion conductor, characterized in that: The core-shell structured hydrogen anion conductor comprises a core portion and a coating layer, wherein the coating layer is coated on the core portion; The core part is a mixed ion conductor that conducts negative hydrogen ions.

2. The hydrogen anion conductor according to claim 1, characterized in that The carriers of the mixed ion conductor are electrons and hydrogen anions, and the ion migration number is 0.01 to 0.

99.

3. The hydrogen anion conductor according to claim 1, characterized in that The core part is a particle with a diameter of 0.01nm to 1mm; the thickness of the coating layer is 0.001nm to 1mm.

4. The hydrogen anion conductor according to claim 1, characterized in that The electronic resistivity of the coating layer at the operating temperature is 100 to 100,000 times that of the core.

5. The method for preparing a hydrogen anion conductor according to any one of claims 1 to 4, characterized in that: The preparation method comprises: A mixture containing rare earth metal hydride and main group metal compound is mixed to obtain the core-shell structured hydrogen anion conductor; The main group metal compound is an alkali metal compound and / or an alkaline earth metal compound.

6. The preparation method according to claim 5, characterized in that: The hybrid construction method is selected from at least one of ball milling, grinding, wet chemical method, and vapor deposition method; Preferably, the ball milling conditions are: the ball milling speed is 50 to 500 rpm, and the ball-mass ratio is 1:1 to 100:1; Preferably, the ball milling atmosphere partial pressure is 0.1 to 100 bar, and the ball milling time is 0.1 to 60 h; Preferably, the grinding atmosphere is selected from hydrogen and / or argon.

7. The preparation method according to claim 5, characterized in that: The conditions of the wet chemical method are: the mixture contains a solvent, and the solvent is selected from at least one of tetrahydrofuran, cyclohexane, and benzene.

8. The preparation method according to claim 6, characterized in that: The reaction temperature in the wet chemical method is -100 to 900°C; Preferably, the reaction atmosphere in the wet chemical method is selected from hydrogen and / or argon.

9. The preparation method according to claim 5, characterized in that: The conditions of the vapor deposition method are: the temperature is -100 to 900° C., and the deposition atmosphere is selected from hydrogen and / or argon.

10. Use of the core-shell structured hydrogen anion conductor according to any one of claims 1 to 4 in novel secondary batteries, fuel cells, hydrogen separation membranes, sensors, and membrane reactors.